Impact of a Historical Fire Event on Pyrogenic Carbon Stocks and Dissolved Pyrogenic Carbon in Spodosols in Northern Michigan - Santos, Fernanda; Wagner, Sasha; Rothstein, David; Jaffe, Rudolf; Miesel, Jessica R. (Frontiers in Earth Science, 2017)
Inventories of fire-derived (pyrogenic) C (PyC) stocks in soils remain incomplete for many parts of the world, yet are critical to reduce uncertainties in global PyC estimates. Additionally, PyC dynamics in soils remain poorly understood. For example, dissolved PyC (DPyC) fluxes from soil horizons, as well as the influence of historical fire events on these fluxes and soil PyC stocks remain poorly quantified. In this study, we examined stock and concentration differences in soil PyC and leached DPyC, respectively, between two forest types in the Great Lakes region (USA): (1) a red pine (Pinus resinosa) forest planted after the site had experienced post-logging slash burning in the late 19th century (100yr-burned site), and (2) a sugar maple (Acer saccharum) forest that showed no evidence of burning in the past 250 years (unburned site). We hypothesized that the 100yr-burned site would have greater PyC stocks and concentrations of DPyC compared to the unburned site. We measured PyC in soil, as well as DPyC in soil water leaching from O and E horizons following a spring snowmelt event in both 100yr-burned and unburned sites. Additionally, we measured DPyC drained from B horizons in 100yr-burned site. In organic horizons, PyC stocks were 1.8 (Oi) and 2.3 (Oe) times greater in the 100yr-burned site than in the unburned site. Contrary to our initial hypothesis, DPyC concentrations did not differ between sites. On average, DPyC leached from all sites contributed 3.11±0.27% of the total dissolved organic carbon pool. In the 100yr-burned site, a significant decline in concentrations of DPyC leaving the B horizon was attributed to the immobilization of this C pool in the Al and Fe oxides-rich subsoil. Even though PyC stock in O horizons was higher in 100yr-burned than in unburned site, our results did not support our initial hypothesis that the 100yr-burned site would have greater DPyC concentrations than the unburned site, suggesting that any differences in DPyC resulting from a single fire event are either not detectable after >100 years post-burn, and/or that the release of DPyC is a continuous, long-term process resulting from the degradation of historically accumulated PyC.